Key issues in the management of cervical cancer: consensus recommendations by a Brazilian expert panel - Eduardo Paulino; Glauco Baiocchi; Agnaldo Lopes Silva; Aknar Calabrich; Andre Lopes; Andrea Paiva Gadelha Guimarães; Andreia Cristina Melo; Angelica Nogueira-Rodrigues; Carla Rameri Azevedo; Carlos Eduardo da Cunha Mattos Andrade; Daniele Xavier Assad; Denise Ferreira Silva Alves; et al. (Brazilian Journal of Oncology)
Objective: We report the results of a panel of Brazilian experts and provide recommendations for the management of these patients. Material and Methods: The panel convened composed by 28 local opinion leaders, addressed 59 multiple-choice questions taking into account the published scientific literature and their own clinical experience. The level of agreement among panel members was qualified as (1) consensus, when at least 75% of the voting panel members; (2) majority vote (50%-74.9%); or (3) less than majority vote. Results: There was at least majority vote for eight of 10 questions on staging and follow-up; for 14 of 23 questions on the treatment of early-stage disease; for 12 of 14 questions related to the treatment of locally-advanced disease; and for seven of the 12 questions related to the treatment of recurrent/metastatic disease. Conclusion: The current recommendations may help practitioners from Brazil and other countries to improve the care they provide to patients.